The use of flunixin meglumine and dexamethasone in acute noninfectious keratoconjunctivitis traumatica - Yılmaz Koç; Mustafa Kul; Fahrettin Alkan (Eurasian Journal of Veterinary Sciences)
This study was conducted on those animals with acute noninfectious keratoconjunctivitis caused by plant materials Nonsteroidal (flunixin meglumine) and steroidal (dexamethasone) treatments were given to help reduce the inflammatory reactions on 34 clinical patients; 30 of which is iamb, 2 are calves, 1 is a goat and 1 is a dog. In addition to this, 8 experimental study were done using dogs totaling 42 animals.